2023
DOI: 10.1101/2023.10.31.560822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical role of CD206+ macrophages in promoting a cDC1-NK-CD8 T cell anti-tumor immune axis

Arja Ray,
Kenneth H. Hu,
Kelly Kersten
et al.

Abstract: Tumor-associated macrophages (TAMs) are frequently and simplistically categorized as immunosuppressive, and one molecule prominently used to highlight their so-called ‘M2’ state is the surface protein CD206. However, direct evidence of the impact of macrophages remains impaired by the lack of sufficiently penetrant and specific tools to manipulate them in vivo. We thus made a novel conditional CD206 knock-in mouse to specifically visualize and/or deplete these TAMs. Early depletion of CD206+ macrophages and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Although we and others use the term “M1-like” and “M2-like” to describe features that at least partially overlap with M1 or ‘classically’ activated and M2 or ‘alternatively’ activated macrophages, this is an oversimplification due to the complexity of activation and functional states of intratumoral macrophages 58 . Further, it is also important to note that although CX3CR1 + CD206 + macrophages display expression patterns consistent with immunosuppressive macrophages, CD206 alone is not sufficient to distinguish macrophages as immunosuppressive 59 , as we observed CD206 expression on some macrophages expressing iNOS. Nevertheless, it is tempting to speculate that combining NeoAg vaccines that maintain or promote CX3CR1 + CD206 + macrophages expressing high levels of Trem2 with treatments targeting this macrophage population might enhance the efficacy of NeoAg vaccines.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although we and others use the term “M1-like” and “M2-like” to describe features that at least partially overlap with M1 or ‘classically’ activated and M2 or ‘alternatively’ activated macrophages, this is an oversimplification due to the complexity of activation and functional states of intratumoral macrophages 58 . Further, it is also important to note that although CX3CR1 + CD206 + macrophages display expression patterns consistent with immunosuppressive macrophages, CD206 alone is not sufficient to distinguish macrophages as immunosuppressive 59 , as we observed CD206 expression on some macrophages expressing iNOS. Nevertheless, it is tempting to speculate that combining NeoAg vaccines that maintain or promote CX3CR1 + CD206 + macrophages expressing high levels of Trem2 with treatments targeting this macrophage population might enhance the efficacy of NeoAg vaccines.…”
Section: Discussionmentioning
confidence: 75%
“…We observed multiple intratumoral monocyte/macrophage clusters in Y1.7LI displaying a range of phenotypic states 58,59 ( Figures 6A, 6B, and S11 ). Ccr2 + M_c1 displayed transcripts consistent with monocytes, including Ccr2 and Chil3 , and the frequency of cells within this cluster only increased slightly with anti-PD-1 or neo VAX ( Figures 6B, 6C, and S11 .)…”
Section: Resultsmentioning
confidence: 98%
“…Specific macrophage subsets co-expressing CD206 and SERPINH1 or MORC4 were connected with positive patient prognosis in breast cancer [ 8 ]. In pre-clinical studies, CD206 TAMs were found to be the primary source of CXCL9—the well-established chemoattractant for CXCR3-expessing NK and CD8 T cells, driving anti-tumor immunity [ 39 ]. CD206 TAMs were also shown to have effective antigen cross-presentation capabilities, leading to tumor antigen-specific CD8 T-cell activation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%